Current diagnosis & treatment in family medicine - South-Paul, Jeannette E.; Matheny, Samuel C.; Lewis, Evelyn L., M.D (McGraw-Hill Education, 2015)
This edition is an easy-to-use guide to the diagnosis, treatment, and management of the full range of clinical conditions seen in primary care. The book covers all age groups--from pediatric to geriatric--and includes end-of-life issues.